Odonata of Costa Rica: Diversity and checklist of spedes - Ramírez, Alonso (2000)
An updated list of the Odonata of Costa Rica is presented containing 268 species. Sínce !he last publíshed lisl for the country, 41 additional species have been reported. The country is !he best studied in Central America. The mos! species-rich families are Libellulidae, Coenagrionidae, Gomphidae, and Aeshnidae, together comprising -75% of the total fauna. Mos! species in the country are a1so found in South America, indicating a tendency for wide ranges rather than endemism. However, about a fifth of !he species appear lo be endemic to the Costa Ríca-Panama region. Estimates of ¡he range of ¡he proportion of total world species occurring in Costa Rica lead lO predictions of a range of 5 600-9 000 species of Odonata worldwide.